2016
DOI: 10.2134/jeq2015.05.0246
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Extraction and Detection of Veterinary Antibiotics in Solid and Liquid Fractions of Manure

Abstract: Analysis of veterinary antibiotics in separated liquid and solid fractions of animal manures is vital because of wide variations in the composition of agriculturally applied manure. Differentiation of antibiotic concentrations is important between liquid and solid manures, as their sorption onto the solid fraction depends on physicochemical properties of each antibiotic and manure composition (e.g., organic content, pH) and because each fraction may be treated and reused differently. Here, an efficient and sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…A separate LC-MS/MS method was adapted from Wallace and Aga42 for macrolide antibiotics to enhance sensitivity. All analytes were normalized to the internal standard d 10 -carbamazepine (sulfonamides and macrolides) or minocycline (tetracyclines).…”
Section: Methodsmentioning
confidence: 99%
“…A separate LC-MS/MS method was adapted from Wallace and Aga42 for macrolide antibiotics to enhance sensitivity. All analytes were normalized to the internal standard d 10 -carbamazepine (sulfonamides and macrolides) or minocycline (tetracyclines).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were analyzed for nine sulfonamide, seven tetracycline, and nine macrolide antibiotic residues using liquid chromatography with tandem mass spectrometry (LC-MS/MS), following the methods of Wallace and Aga (2016). While β-lactams were used in the herd, these antibiotics were not analyzed based on our preliminary studies that showed non-detection in manure.…”
Section: Antibiotic Usage and Residue Detectionmentioning
confidence: 99%
“…Studies have shown some persistent antibiotic residues (e.g. tetracyclines, macrolides) adsorb to organics and are detected at higher concentrations in dairy manure solids (Wallace & Aga, 2016;Hurst et al, 2018). There is also evidence that SLS technologies can reduce the occurrence of bovine pathogens (Liu et al, 2017), and ARGs (Tien et al, 2017;Wallace et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic residues were extracted and analyzed for select Sulfonamides, Macrolides, and Tetracycles similarly to the methods of Wallace & Aga (2016). Frozen manure samples were freeze dried, homogenized and 100 mg of dried manure solids were added to a polypropylene centrifuge tube.…”
Section: Antibiotic Residuesmentioning
confidence: 99%